The current political situation in Chile and the government of the «new majority» - L. V. Diakova (Ибероамериканские тетради, 2015)
The article discusses the current political situation in Chile and the results of the first year in power of Michelle Bachelet second government; analyzes problems and risks of this period associated with increasing political instability. The author points out that high social expectations of the part of society, requiring an accelerated pace of reforms, do not always contribute to the formation of the balanced and adequate political strategy.